Initiation Economic Information for Decision Making Process in Housing Development - Rozlin Zainal; Fazian Hashim; Sharifah Meryam Shareh Musa; Seow Ta Wee; Zarina Shamsudin; Noralfishah Sulaiman (International Journal of Supply Chain Management, 2019)
Conflict communication among developer and their team at all times happened due to limited financial information. A developer does not automatically construct a unit that will convince the recipients since they have their own viewpoint and mind of their needs, objectives, obstructions, and necessities of economic aspect. A decision is very hard to be made on the housing unit since the recipients have variance on numerous economic issues. This paper aims to identify the economic decision making information for housing development at the initiation phase in Malaysia. Delphi method is implemented in 3 rounds using a questionnaire survey which involved 34 private developers for data collection purposes. The finding shows that authority policies, a market of housing and timing (life cycle of a project) are most necessary information in the economic part. All of the economic information also illustrates that they are crucial and key factors in the decision-making process. The stages in the initiation phase require economic information in the form of a qualitative data bank of a developer.